Adverse Effects of Immobilised Pseudoalteromonas on the Fish Pathogenic Vibrio anguillarum: An In Vitro Study. (5th September 2016) - Wesseling, Wiebke; Lohmeyer, Michael; Wittka, Sabine; Bartels, Julia; Kroll, Stephen; Soltmann, Christian; Kegler, Pia; Kunzmann, Andreas; Neumann, Sandra; Ramsch, Burkhard; Sellner, Beate; Meinhardt, Friedhelm
Abstract : As a prerequisite for use in marine aquaculture, two immobilisation systems were developed by employing the probiotic bacterium Pseudoalteromonas sp. strain MLms_gA3. Their impact on the survivability of the fish pathogen Vibrio anguillarum was explored. Probiotic bacteria either grown as a biofilm on ceramic tiles or embedded in alginate beads were added to sterile artificial seawater that contained the fish pathogen. While immobilisation on ceramics followed a recently developed protocol, a medium allowing for alginate microencapsulation was newly developed. Anti- Vibrio activities were obtained with both immobilisation systems. The viable cell counts of V. anguillarum constantly decreased within the first two weeks of the treatments evidencing the potential of the immobilisation systems for providing probiotic-based protection against this pathogen.